Taḥlīlu al-ʾAkẖṭāʾ al-Naḥwiyyah Limādati al-Insyāiʾ al-Faṣli al-Rābiʿ al-Dīnīyah Limaʿhadi Taḥfīẓ Al-Qurʾān Lilbanāti Al-Amien Prenduan Sumenep Madura - Mubayyinah Hasanah; Saiful Anam (KURAS Institute, 2023)
This paper is based on a problem that occurred in class Grade Four of Madrasah Diniyah Pondok Pesantren Tahfidz Al-Qur'an Lilbanat Al-Amien Prenduan academic year 2021-2022. Authors found that learning insya’ material in that was less effective, this paper aims to find out how nahwu errors form in insya' material Grade Four of Madrasah Diniyah Pondok Pesantren Tahfidz Al-Qur'an Lilbanat Al-Amien Prenduan, what are the factors that cause nahwu errors in insya' material, and what are the solutive efforts to minimize nahwu errors in insya' material. The method used is qualitative research with a descriptive research type, the data analysis carried out is collecting data, identifying errors, classifying errors, explaining errors, and using observation, interview, and documentation methods. The results obtained in this study are First, the nahwu errors that occurred in Grade Four of Madrasah Diniyah Pondok Pesantren Tahfidz Al-Qur'an Lilbanat Al-Amin Prenduan are writing the perfect sentence or jumlah mufidah/tarkibul jumal, using zamir, using idafah arrangements, writing na'at and man'ut arrangements, and writing i'rab signs. Second, the factors that cause nahwu errors in insya' material are internal factors and external factors. Internal factors include the lack of student interest in learning the material of insya', lack of theoretical understanding of the nahwu rules in insya' material, lack of knowledge about mufradat (vocabulary), and afraid of speaking in Arabic. External factors include inadequate time allocation and non-conducive class situations. Solutive efforts to minimize mistakes in writing insya' are familiarizing students speaking Arabic in class, increasing practice or work on questions, correcting immediately, and re-teaching the wrong material.